Medical Record Audit of Patients with Diabetes Mellitus, Gastroenteritis, and Pneumonia: Audit Rekam Medis Pasien Diabetes Mellitus, Gastroenteritis, dan Pneumonia - Safitri, Eka Nur; Tajuddin, Mohammad; Nisak, Umi Khoirun (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Hospitals provide comprehensive health services and require complete medical record documentation to ensure quality care and accreditation. Specific Background: Incomplete medical records reduce the reliability of health data and hinder administrative and insurance processes. Knowledge Gap: Limited studies have analyzed the completeness of inpatient medical records for specific diseases in Indonesian hospitals. Aims: This study aims to analyze the completeness of medical record audits for patients with Diabetes Mellitus, Gastroenteritis, and Pneumonia at Bhayangkara Pusdik Shabara Porong Hospital. Results: Quantitative analysis of 76 inpatient records (34 Diabetes Mellitus, 25 Gastroenteritis, and 17 Pneumonia) from October 2021–October 2022 revealed that the completeness of social data review was 23.7%, record evidence 30.3%, record validity 67.1%, and recording procedure 56.6%. Novelty: The study provides a disease-specific evaluation of medical record completeness using standardized criteria. Implications: Findings highlight the need for continuous audits to improve documentation accuracy, ensure compliance with accreditation standards, and support hospital administration. Highlights: Medical record audits revealed low completeness in social data and record evidence. Record validity was relatively higher but still below standard requirements. Continuous audits are essential for accreditation and service quality improvement. Keywords: Hospital, Medical Record Audit, Diabetes Mellitus, Gastroenteritis, Pneumonia